Chromatin Dynamics in Digestive System Cancer: Commander and Regulator - Li, Zeru; Zhao, Bangbo; Qin, Cheng; Wang, Yuanyang; Li, Tianhao; Wang, Weibin (Frontiers in Oncology, 2022)
Digestive system tumors have a poor prognosis due to complex anatomy, insidious onset, trouble in early diagnosis, and chemoresistance. Epidemiological statistics let see that digestive system tumors rank first in tumor-related death. Although a greatly sized number of studies have been devoted to the molecular biological mechanism, early diagnostic markers and application of new targeted drugs in digestive system tumors, the therapeutic effect is still not satisfactory. A fundamental trait of virtually all gastrointestinal cancers is epigenomic alterations. Chromatin is the carrier of genetic information and consists of DNA, histones, non-histone proteins and a small amount of RNA. Chromatin and nucleosomes control the stability of eukaryotic genome and regulate DNA processes such as transcription, replication and repair. Dynamic structure of chromatin plays a key role in this regulatory function. Structural fluctuations expose internal DNA and thus provide access for the nuclear machinery. The dynamic changes are affected by various complexes and epigenetic modifications. Variation of chromatin dynamic produces early and superior regulation of the expression of related genes and downstream pathways, thereby controlling tumor development. Intervention at the chromatin level can change the process of cancer earlier and is a feasible option for future tumor diagnosis and treatment. In this review, we introduced chromatin dynamics including chromatin remodeling, histone modifications and chromatin accessibility, current research on chromatin regulation in digestive system tumors were also summarized.